(untitled) (Global Journal of Human-Social Science, 2016)
The novel under-study is Mohsin Hamid’s How to Get Filthy Rich in Rising Asia. The study is an attempt to seek answer to the question as to whether the novel can be termed as a ’social satire’ or not; and whether it is set in contemporary Pakistan or otherwise. This question precisely governs the overall research. The analysis shows that the novel under-study tacitly satirizes the social institutions of the country it is set in. It has been found that it holds the social wrongs of various institutions up to ridicule more than the individual follies. The targets of the attack are social areas like health, education, bureaucracy, industry etc., and sufficient textual proofs support the same. So it can safely be termed as a social satire. As far the unnamed place is concerned, the textual evidences and analysis of secondary sources particularly regarding the level, nature and frequency of ills like corruption, nepotism, terrorism and insecurity corroborate that the novel is set in contemporary Pakistan.